Streptococcus pneumoniae infections in an adult intensive care unit: A retrospective study from a tertiary Center in Portugal - Ana Catarina Rodrigues Gonçalves; Diogo Costa Oliveira; Rita Jorge; José Chen-Xu; Matilde Couto; Isabel Campos; José Artur Paiva (Vaccine: X)
Introduction: Streptococcus pneumoniae (SP) infections and invasive pneumococcal diseases (IPD) are major contributors to morbidity and mortality in Europe. Vaccination is one of the most effective methods in preventing IPD. It is important to understand the impact of vaccination on patients admitted to the intensive care unit (ICU) with pneumococcal disease and to evaluate if further populational studies are necessary to guarantee better clinical outcomes. Objective: This study aimed to assess vaccination status in adults (≥ 18 years old) ICU patients with SP infection and evaluate risk factors, mortality, and outcomes related to pneumococcal disease. Subgroup analysis focused on patients with IPD. Methods: A retrospective study was conducted on adult ICU patients with SP infection in a Portuguese tertiary hospital from August 2018 to August 2023. Data on serotypes, antimicrobial susceptibility, and vaccination status were analysed using statistical methods. Results: During the study period, 105 patients with confirmed SP infection were included, with a mean age of 62.5 years and a predominance of males (67.6 %). Arterial hypertension (52.4 %) and type 2 diabetes (23.8 %) were the most common comorbidities. In-hospital mortality was 13.3%, and 35.2 % of patients required invasive mechanical ventilation. Immunosuppression was significantly associated with both higher in-hospital mortality (p = 0.028) and the development of IPD (p = 0.012). Vaccination was associated with a reduced need for invasive mechanical ventilation (p = 0.043). Despite 94.8 % of patients meeting vaccination criteria, the overall vaccination rate was low (21.9 %). Discussion and conclusion: Immunocompromised patients face a significantly higher risk of invasive pneumococcal disease and in-hospital mortality, highlighting the need for more effective vaccination strategies. Despite established national guidelines, vaccination coverage remains inadequate, emphasizing the necessity of targeted interventions. Vaccination was significantly associated with a reduced need for invasive mechanical ventilation. Additionally, our findings suggest that the complete PCV13 + PPSV23 vaccination scheme may be linked to lower mortality rates; however, the sample size was insufficient to establish a significant correlation. Enhanced surveillance and serotype studies are essential for addressing the burden of pneumococcal disease more effectively.